Numerical Investigation of Seismic Demands in Floor Diaphragms and Collectors - Sheykhaleslami, Alireza; Maleki, Shervin (Engineering Science & Technology, 2026)
This study investigates the seismic demand in diaphragms, chords, and collectors in typical floor systems used in steel structures using nonlinear Finite Element (FE) analyses. These systems include prefabricated one-way steel joist floor systems, open-web steel joists, and composite steel decks. The Lateral-Force-Resisting Systems (LFRSs) considered were Special Concentrically Braced Frames (SCBFs) and Special Moment Frames (SMFs) of varying heights. For each system, the effects of using shear connectors for collector beams, joist direction, geometric configuration, and number of stories on lateral force transfer were examined. Analyses were conducted on selected models. The study shows, in steel joist floor systems without shear connectors on collector beams, the diaphragm force transfer path is significantly influenced by joist orientation. Furthermore, using shear connectors on collectors bypasse joist participation in lateral load transfer, allowing the floor slab to transmit forces directly to the LFRS like a rigid diaphragm through the collectors. In composite steel decks, using shear connectors on collector beams was found to improve diaphragm ductility and cyclic performance. Overall, the study clarifies the true structural role of diaphragms, demonstrating that without proper analysis models, seismic load paths can become disrupted and traditional design assumptions may fail to ensure structural safety. The findings indicate that the introduction of diaphragm-specific response modification factors of one or less (Rs ≤ 1) results in more realistic diaphragm forces. Applying the outcomes of this research will align diaphragm design practice more closely with the actual behavior.